Separability of local reactivity descriptors - Tanwar, A; Pal, S (Journal of Chemical Sciences, 2005)
The size-dependence of different local reactivity descriptors of dimer A(2) and AB type of systems is discussed. We derive analytic results of these descriptors calculated using finite difference approximation. In particular, we studied Fukui functions, relative electrophilicity and relative nucleophilicity, local softness and local philicity. The results are explained using the example of the dimer of BH3NH3.
Keywords: condensed Fukai functions; Local reactivity descriptors; molecular interactions; separability